Everyday Place Making Through Social Capital Among Street Vendors at Manek Chowk, Gujarat, India - P., Neethi and Kamath, Anant and Paul, Anjali M. (Space and Culture, 2021)
This is a novel interpretation of the dynamics of the historic market of Manek Chowk in Ahmedabad in Gujarat, India. Applying elements of spatial ethnographic methodology, we capture the processes, routines, and unique features of operation among the myriad actors operating here, and the frictionless multiple transformation of this traditional market within the course of a full day. These findings are viewed through the critical geography concept of place making, which is realized to be supported by the economic sociology concept of social capital. In this process of offering a fresh understanding, we examine the meanings that people here have attached to this locale, given their operation here for several decades and across generations. We realize that this traditional market with its characteristic dynamism is not just a commercial space but an entity intertwined with physical elements, activities, relationships, and constructed meanings. Hence, we offer a fresh interpretation of the character and vibrancy of Manek Chowk by understanding its continuing life and sustenance as a social capital–bolstered place-making process.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMjA2MzMxMjE5ODMwMDc5